1994
DOI: 10.4992/psycholres1954.36.188
|View full text |Cite
|
Sign up to set email alerts
|

Perception of illusory contour and spatio-temporal integration in the visual system

Abstract: Spatial and temporal conditions to perceive an illusory contour figure were examined. Six figural elements inducing an illusory figure were successively presented. Total time to present all inducers and the ratio of duration to 1S1 between inducers were systematically varied. Five subjects were required to rate the clarity of illusory contour, brightness difference and apparent depth difference on an 11 point scale. The effects of total time and the ratio of duration to ISI were significant. The results of cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
6
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Taking into consideration the difference in the temporal characteristics of the contour system and the surface‐spreading system (Ringach & Shapley, 1996), the surface‐spreading system might operate in the 240‐ms condition. The notion of the difference of the temporal characteristics of the contour system and the surface‐spreading system is consistent with the estimates of spatiotemporal integration, approximately 300 ms, using brightness change as a measure (Takemoto & Ejima, 1997; Unuma & Tozawa, 1994). The unit representation of objects (Kellman et al., 1998, 2001) might be related to such a surface representation.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Taking into consideration the difference in the temporal characteristics of the contour system and the surface‐spreading system (Ringach & Shapley, 1996), the surface‐spreading system might operate in the 240‐ms condition. The notion of the difference of the temporal characteristics of the contour system and the surface‐spreading system is consistent with the estimates of spatiotemporal integration, approximately 300 ms, using brightness change as a measure (Takemoto & Ejima, 1997; Unuma & Tozawa, 1994). The unit representation of objects (Kellman et al., 1998, 2001) might be related to such a surface representation.…”
Section: Discussionsupporting
confidence: 77%
“…There is evidence that spatiotemporal integration is temporally limited to relatively brief time intervals (Shipley & Kellman, 1994; Takemoto & Ejima, 1997; Unuma & Tozawa, 1994). For instance, Shipley and Kellman (1994) examined boundary formation and shape identification using spatiotemporal transformations of spatially separated elements, and found that spatiotemporal integration appears to be less efficient when temporal ranges exceed 165 ms. Unuma and Tozawa (1994) used a serial presentation paradigm in which each inducing part of an illusory contour figure was presented individually in a particular serial order, and analyzed causal relations between perceived brightness‐change, contour‐clarity, and depth‐change. They found that an illusory contour figure could be perceived from fragmented edges within a total temporal range that was greater than 260 ms, as given by the stimulus‐onset asynchrony (SOA) between two successive inducing elements.…”
mentioning
confidence: 99%
See 3 more Smart Citations